Three retinoid X receptor gene polymorphisms in plaque psoriasis and psoriasis guttata - Vasků, Vladimír; Bienertová Vasků, Julie; Pávková Goldbergová, Monika; Vasků, Anna (Dermatology (Basel, Switzerland), 2007)
AIM: Polymorphisms in retinoid X receptors (RXRs) are very interesting from the point of view of a possible association of their variability with psoriasis. METHODS: A total of 293 patients with plaque psoriasis, 82 patients with psoriasis guttata and 202 control subjects were enrolled in this study focused on 3 polymorphisms in RXRA and RXRB gene associations. RESULTS: A marginally significant increase in AA allelic frequency of the RXRA A39526AA polymorphism in plaque psoriatic men compared to healthy men was proved. In women with psoriasis guttata, the higher risk for genotypes AA and TT in the RXRB 3'+140A/T polymorphism compared to healthy women was identified (p(corr) = 0.01). The genotypes A/A and AA/AA are more frequent in plaque psoriasis patients with a positive family history of psoriasis compared to the patients with a negative family history of psoriasis (p(corr) = 0.02). The A/A genotype is more frequent in patients with plaque psoriasis and repeated tonsillitis/tonsillectomy (p = 0.02). In the RXRB polymorphism, no genotype TT is observed in patients with psoriasis guttata with a positive personal history of repeated tonsillitis (p(corr) = 0.001). CONCLUSION: Individual gene characteristics of patients with psoriasis improve the possibilities of pharmacotherapy using pharmacogenomic approaches which could be further stratified in future according to the subtypes of psoriasis.
Keywords: RNA, Messenger; Gene Frequency; Male; psoriáza; Genotype; polymorfismus genetický; retinoidní X receptor beta; Adolescent; Adult; Aged; dospělí; Case-Control Studies; mužské pohlaví; senioři; messenger RNA; Polymorphism, Genetic; Angiotensinogen; mladiství; Retinoid X Receptor alpha; Retinoid X Receptor beta; frekvence genu; tonzilitida; senioři nad 80 let; lidé; Psoriasis; ženské pohlaví; studie případů a kontrol; retinoidní X receptor alfa; Humans; Retinoid X Receptors; Aged, 80 and over; genotyp; angiotensinogen; Female; lidé středního věku; retinoidní X receptory; Tonsillitis; Middle Aged